The Correlation between Students’ Digital Literacy and English Communicative Competence - Nur Ekaningsih; Cikal Kurnia (Universitas Bengkulu, 2022)
In this globalization era, students are forced to understand the basic knowledge of digital literacy because of the transformation in the learning activity. Therefore, digital literacy also can be the medium to learn and develop students’ English communicative competence. English communicative competence can be accomplished in many ways, but digital literacy is also taking a serious role in it. This study pointed to discover the correlation between students’ digital literacy and English communicative competence. This study used a closed-ended questionnaire and an open-ended interview as instruments for a correlational investigation that was linked to a quantitative study. The participants in this study were fourth-semester UNISSULA English Education understudies. The results of this study revealed a shaky link between students' digital literacy and English communicative skills. It was established that the correlational coefficient value was less than the r table score of 0.350 0.432, which is between 0.20 and 0.399 in terms of correlation coefficient interpretation. It can be described that the correlation coefficient between students’ digital literacy and English communicative competence is weak. Although the correlation was weak, but digital literacy had an essential impact on students’ English communicative competence. Then, it can also be said that H1 is accepted and H0 is rejected.